Gród w Dobromierzu- próba rekonstrukcji - Małachowicz, Maciej; Małachowicz, Anna
In 2018, at the request of the Dobromierz Commune, we made an attempt to create a project of an archaeological exhibition in the stronghold together with a partial reconstruction of the complex. The article presents the results of the re-analysis of discovered relics using architectural research methods. The result is a reconstruction in the form of a drawing of the likely architecture of the establishment. According to the authors, an attempt to show the elements that have not been preserved allows us to expand our knowledge about the forms of reconstructed buildings and verify the existing reconstructions.
Keywords: exposure; the stronghold; archeology